CEPHALOPOD RESOURCES OF THE SOTH SULAWESI SEAS - Abdul Ghofar (JOURNAL OF COASTAL DEVELOPMENT, 1998)
A study was conducted in South Sulawesi including Takaboberate Islands and adjacent areas from October 1994 to March 1995 to describe the cephalopod fauna in the area and to assess the status of their utilization. Six major observations and specimen collection were carried out around Pulau-pulau Selayar, Rajuni, Tinanja, Taka Lamungan, Tarupa and landing places in Ujung Pandang and Pare-pare. Most observations were made by means of snorkeling. Identification of specimens were carried out upon fresh specimens, which were then preserved in 4% formalin for 1-2 day depending on their size, prior to transporting for further laboratory observations and deposition. Fifteen species of cephalopods, representing 4 species of the family Loliginidae, 1 species of Enoploteuthidae, 7 species of Sepiidae, 1 species of Octopodidae, and 2 species of Nautilidae were identified. During the survey, spawns of 2 species of family Sepiidae were also collected, however there were no strong evidence of the occurrence of spawning ground for the species in the area, at least during the period of survey. The MSY for squid was estimated to be 1.840 ton per year, corresponding to an optimum effort of 4.800 bagam-prahu. Further increase intensity is possible, although a cautious management required, including continuous monitoring of the fishery and squid biology.